Detection of polyomavirus bk reactivation after renal transplantation using an intensive decoy cell surveillance program is cost-effective - Chakera, Aron; Dyar, O.; Hughes, E.; Bennett, S.; Hughes, D.; Roberts, I. (2011)
BACKGROUND.: Reactivation of polyomavirus BK (BKV) after renal transplantation can lead to allograft dysfunction or loss with early detection improving outcomes. Current guidelines recommend quantitative polymerase chain reaction for surveillance; however, urinary decoy cell detection is a potentially cost-effective alternative. We present the outcomes from an early intensive BKV surveillance program using decoy cell detection for initial screening starting 2 weeks after transplantation. METHODS.: Records for all recipients of kidney (n=211) or simultaneous kidney and pancreas (n=102) transplants performed over 2 years in a single center were reviewed. Follow-up was for a minimum of 1 year. Urine cytology screening was performed fortnightly from 0 to 3 months after transplantation, monthly from 3 to 6 months then every 2 months from 6 to 12 months. RESULTS.: Decoy cell positivity occurred in 56 of 313 patients (17.9%) with sustained decoy cell positivity (2 positive urine samples >2 weeks apart) present in 32 patients (10.2%). Twenty-four patients (7.6%) became viremic and three patients (1%) developed polyoma virus nephropathy. The median time after transplantation until decoy cell positivity was 78 days, decreasing to 67 days for patients with sustained positivity and 57 days for patients who developed polyoma virus nephropathy. No grafts were lost due to BKV during the study period. Decoy cell screening resulted in savings of approximately £135,000 over 2 years, when compared with routine surveillance by quantitative polymerase chain reaction. CONCLUSIONS.: Clinically significant BKV reactivation occurs early after transplantation and can be reliably detected by decoy cell screening. A surveillance strategy for detecting BKV reactivation based on urine cytology is cost-effective. Copyright © 2011 by Lippincott Williams & Wilkins.